Oxypurinol protects renal ischemia/reperfusion injury via heme oxygenase-1 induction - Kang, Hye Bin; Lim, Chae Kyu; Kim, Jongwan; Han, Sang Jun (Frontiers in Medicine, 2023)
Renal ischemia/reperfusion (I/R) injury is a major cause of acute kidney injury (AKI) by increasing oxidative stress, inflammatory responses, and tubular cell death. Oxypurinol, an active metabolite of allopurinol, is a potent anti-inflammatory and antioxidant agent. To investigate the therapeutic potential and underlying mechanism of oxypurinol in ischemic AKI, C57BL/6 male mice were intraperitoneally injected with oxypurinol and subjected to renal I/R or sham surgery. We found that oxypurinol-treated mice had lower plasma creatinine and blood urea nitrogen levels and tubular damage (hematoxylin-and-eosin staining) compared to vehicle-treated mice after renal I/R injury. Furthermore, oxypurinol treatment reduced kidney inflammation (i.e., neutrophil infiltration and MIP-2 mRNA induction), oxidative stress (i.e., 4-HNE, heme oxygenase-1 [HO-1], 8-OHdG expression, and Catalase mRNA induction), and apoptosis (i.e., TUNEL or cleaved caspase-3-positive renal tubular cells), compared to vehicle-treated mice. Mechanistically, oxypurinol induced protein expressions of HO-1, which is a critical cytoprotective enzyme during ischemic AKI, and oxypurinol-mediated protection against ischemic AKI was completely eliminated by pretreatment with tin protoporphyrin IX, an HO-1 inhibitor. In conclusion, oxypurinol protects against renal I/R injury by reducing oxidative stress, inflammation, and apoptosis via HO-1 induction, suggesting its preventive potential in ischemic AKI.